Reducing climate-induced heat stress in pigs in Uganda: Policy actions - Mutua, John Y.; Zaake, Paul; Notenbaert, An Maria Omer; Paul, Birthe K. (Bioversity International and the International Center for Tropical Agriculture, 2020)
Pig farming is important for income generation and nutrition for a large population in Uganda, with 4.2 million pigs being kept in 2017. However, future projections indicate that domestic pork production will not be sufficient to meet the increasing demand. This situation is likely to be aggravated by climate-induced heat stress. Analysis of mhistorical climate data and simulation of future periods predicts a gradual shift towards more severe heat stress conditions experienced in most parts of the country. Animals experience heat stress when subjected to a series of conditions where the animal’s body is overheating. Pigs are more vulnerable to heat stress because they do not have functioning sweat glands. Heat stress distorts the pigs’ feed intake, growth and reproduction and makes pigs vulnerable to diseases. This, in turn, brings economic losses. In Uganda, smallholder pig production systems -which are the majority- are transitioning towards market-oriented models. However, to remain sustainable, adaptation of these systems to heat stress should be a priority. This policy brief synthesizes research findings on heat stress in pigs in Uganda, reviews proven interventions elsewhere, and concludes with evidence-based policy recommendations. Recommended policy options include prioritization of coordinated national & local level policy making and implementation, promoting heat stress coping and adaptation measures at farm level, action plans at various value chain stages, close research-policy cooperation and information sharing, and action and investment by donors and development organizations. If agricultural extension, policymakers and planners, and development donors and organizations leverage these options, pig farmers will be able to cope, adapt and mitigate heat stress in pigs and the pig production sector in Uganda will become more resilient.